Author Correction: SUMOylation of VEGFR2 regulates its intracellular trafficking and pathological angiogenesis - Huanjiao Jenny Zhou (Nature Portfolio, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.